THE CONTRIBUTION OF AGRICULTURAL BIOTECHNOLOGY TO HOUSEHOLD FOOD SECURITY THROUGH THE ROLE OF WOMEN FARMER GROUPS (WFG) IN SAMUDERA DISTRICT, NORTH ACEH REGENCY - Amilda, Yenny (Universitas Veteran Bangun Nusantara, 2026)
Household food security stands as a strategic issue in agricultural development, particularly in rural areas. One viable measure to enhance food security is through the utilization of agricultural biotechnology and the strengthening of community institutions, specifically Women Farmer Groups (Kelompok Wanita Tani or KWT). This study aims to analyze the role of agricultural biotechnology in supporting household food security through the activities of Women Farmer Groups in Samudera District, North Aceh Regency. This study employed a quantitative approach using a survey method. Primary data were collected via structured questionnaires distributed to KWT members, while secondary data were obtained from relevant agencies and literature reviews. Data analysis was performed descriptively and inferentially to delineate the level of agricultural biotechnology adoption and the respondents' household food security status. The results indicated that the adoption level of agricultural biotechnology among KWT members ranged from moderate to high categories; the most widely utilized technologies included biofertilizers, high-yielding varieties, and microbe-based organic matter management. The majority of respondent households were classified as food secure, whereas a small proportion remained in vulnerable and food-insecure conditions. Furthermore, the findings indicated a positive correlation between the adoption level of agricultural biotechnology and household food security status. This demonstrates that the active involvement of women in KWT, combined with the utilization of agricultural biotechnology innovations, plays a pivotal role in enhancing food availability, access, and utilization at the household level. This study is expected to serve as a basis for policy formulation regarding women's empowerment and sustainable agricultural development in rural areas. Keywords: Agricultural Biotechnology; Women Farmer Groups; Household Food Security.